Use of locally prepared peritoneal dialysis (PD) fluid for acute PD in children and infants in Africa. Issue 5 (September 2020) - McCulloch, Mignon I; Nourse, Peter; Argent, Andrew C
Background: In less well-resourced countries, the high cost of commercially available peritoneal dialysis (PD) fluid limits its use. The major concerns regarding bedside-prepared PD fluid is peritonitis as well as electrolyte disorders. The aim of this study was to review our experience with the use of PD fluids prepared at the bedside using the intravenous infusion solution Balsol (Fresenius Kabi). Methods: This was a retrospective review of all patients who received PD for acute kidney injury (AKI) using a bedside-prepared PD solution adapted from the intravenous solution Balsol in our intensive care unit. Results: In total, 49 cases of acute PD were performed. Of the 49 children, 21 (43%) were male. The ages of the patients ranged from newborn to 10.2 years (median 0.33 years). The weight of children ranged from 1.3 kg to 50 kg (median 4.1 kg). The type of PD catheters used: Cook catheters, 41 patients; Kimal peel-away, 10 patients; and surgical inserted Tenckhoff type of catheter, 2 patients. The duration of PD was 1–17 days (median 3 days) Complications included peritonitis in 2 of 49 patients and blocked catheter in 6 of 49 patients. There were no electrolyte disturbances as a result of the PD. Overall survival was 43% of patients. Conclusions: Locally prepared PD solutions at the bedside adapted from intravenous solutions can be used safely and effectively. This has important relevance for centres in less well-resourced countries, where commercially produced PD fluid is not available for the management of AKI.